2020
DOI: 10.1001/jamainternmed.2019.4802
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Group Medical Visits Combined With Intensive Weight Management vs Group Medical Visits Alone for Glycemia in Patients With Type 2 Diabetes

Abstract: IMPORTANCE Traditionally, group medical visits (GMVs) for persons with diabetes improved glycemia by intensifying medications, which infrequently led to weight loss. Incorporating GMVs with intensive dietary change could enable weight loss and improve glycemia while decreasing medication intensity.OBJECTIVE To examine whether a program of GMVs combined with intensive weight management (WM) is noninferior to GMVs alone for change in glycated hemoglobin (HbA 1c ) level at 48 weeks (prespecified margin of 0.5%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 49 publications
0
53
0
Order By: Relevance
“…However, as metformin was continued the participants did not meet the current definition of remission (box 1). Participants in the intervention group lost 3.7 kg more than those in the comparator group and 11% (12/109) achieved HbA 1c <48 mmol/mol compared with 0/117 in the comparator group 31…”
Section: Key Components Of Dietary Advicementioning
confidence: 97%
“…However, as metformin was continued the participants did not meet the current definition of remission (box 1). Participants in the intervention group lost 3.7 kg more than those in the comparator group and 11% (12/109) achieved HbA 1c <48 mmol/mol compared with 0/117 in the comparator group 31…”
Section: Key Components Of Dietary Advicementioning
confidence: 97%
“…The cost of the REAL HEALTH-Diabetes LI was approximately $1750 per person for 12 months, which is comparable with the cost of other LI programs 22,23 and very similar to a contemporaneous, less intensive, dietitian-delivered VA group medical visit nutrition counseling program (4% mean weight loss at 48 weeks; $1513 per patient per year). 24 This compares favorably to the cost of on-patent weight loss or glucose-lowering medications that are recommended to promote weight loss ($3600-$7200 or more per year for lorcaserin, SGLT2 inhibitors, or GLP-1 receptor agonists). 25 MNT intervention cost is substantially lower than either LI approach.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a high-fat diet has been associated with increased PDAC risk [ 293 ]. In terms of intensive weight management, a recent study showed that low-carbohydrate diets had similar outcomes as with medication [ 296 ]. In terms of chemotherapy (5-FU), PDAC patients with BMI ≤ 25 were found to have a significant survival benefit (median survival increasing significantly by some 50%) which was not seen in patients with BMI > 25 [ 294 ].…”
Section: Lifestyle Factorsmentioning
confidence: 99%